Enhancing the Discovery of Bioactive Secondary Metabolites From Fungal Endophytes Using Chemical Elicitation and Variation of Fermentation Media - Gakuubi, Martin Muthee; Ching, Kuan Chieh; Munusamy, Madhaiyan; Wibowo, Mario; Liang, Zhao-Xun; Kanagasundaram, Yoganathan; Ng, Siew Bee (Frontiers in Microbiology, 2022)
Endophytic microorganisms are an important source of bioactive secondary metabolites. In this study, fungal endophytes obtained from A*STAR’s Natural Product Library (NPL) and previously isolated from different habitats of Singapore were investigated for their diversity, antimicrobial and cytotoxic activities. A total of 222 fungal strains were identified on the basis of sequence analysis of ITS region of the rDNA gene. The identified fungal strains belong to 59 genera distributed in 20 orders. Majority of the identified strains (99%; 219 strains) belongs to the Phylum Ascomycota, while two strains belonged to the phylum Basidiomycota and only one strain was from Mucoromycota phylum. The most dominant Genus was Colletotrichum accounting for 27% of all the identified strains. Chemical elicitation using 5-azacytidine and suberoylanilide hydroxamic acid (SAHA) and variation of fermentation media resulted in a general increase in the number of bioactive strains. Bioassay-guided isolation and structure elucidation of active constituents from three prioritized fungal strains; Lophiotrema sp. F6932, Muyocopron laterale F5912 and Colletotrichum tropicicola F10154 led to the isolation of a known compound; palmarumycin C8 and five novel compounds; palmarumycin CP30, muyocopronol A - C and tropicicolide. Tropicicolide displayed strongest antifungal activity against A. fumigatus with an IC50 value of 1.8 µg/mL but with a weaker activity against the C. albicans presenting an IC50 of 7.1 µg/mL. Palmarumycin C8 revealed the best antiproliferative activity with IC50 values of 1.1 and 2.1 µg/mL against MIA PaCa-2 and PANC-1 cells respectively.